Comparative investigation on the structural, morphological, optical, and magnetic properties of CoFe2O4 nanoparticles. Issue 10 (July 2017) - Kombaiah, K.; Vijaya, J. Judith; Kennedy, L. John; Bououdina, M.; Ramalingam, R. Jothi; Al-Lohedan, Hamad A.
Abstract: Herein, we report a sustainable production of magnetic cobalt ferrite nanoparticles by conventional (CHM) and microwave heating (MHM) method. Hibiscus rosa-sinensis extract was used as both reducing and stabilizing agent. Using plant extracts to synthesize nanoparticles has been considered as an eco-friendly method, since it avoids noxious chemicals. The plethora of plant extract mediated nanoparticles were compared by techniques, such as XRD, Rietveld, FT-IR, SEM, EDX, UV-Visible DRS, PL and VSM were carried out to analyze and understand their crystallite size, functional groups, morphology, optical and magnetic properties. The crystalline structure of cobalt ferrite nanoparticles revealed the cubic structure and the microwave heating of nanoparticles showed smaller crystallite size compared to the conventional heating, which was then confirmed by XRD analysis. To analyze the presence of functional groups and the phytochemical involvement of the plant extract was confirmed by FT-IR studies. Spherical morphology with less than 100 nm sized particles was confirmed by SEM and EDX analysis confirm the existence of Co, O, and Fe elements present in the samples. UV-Visible DRS studies were carried out to calculate the band gap of the as-synthesized nanoparticles, estimated from the Kubelka-Munk function, as 2.06, and 1.87 eV for CHM and MHM, respectively. Photoluminescence emission spectrum of the nanoparticles showed two different bands at 494 and 620 nm, which explores the optical properties of the nanoparticles, due to the quantum confinement effect. VSM analysis showed better ferromagnetic behavior, which can be used for magnetic applications.